2006
DOI: 10.1111/j.1479-828x.2006.00590.x
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and leptin receptor levels in pregnant women with hyperemesis gravidarum

Abstract: It was concluded that leptin could play a role in, and be defined as, a marker of hyperemesis gravidarum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 19 publications
3
15
2
1
Order By: Relevance
“…51 Lower levels of leptin were found in 1 study of 20 patients with HG compared with 20 controls as were higher levels of nesfatin-1, another hormone thought to regulate appetite and weight. 52 Of note, the leptin level results in this study differ from what has previously been reported in the literature 53 ; thus, further studies are needed to determine the role of hunger hormones in HG and whether they can serve as a marker for disease severity.…”
Section: Psychologic Factorscontrasting
confidence: 84%
“…51 Lower levels of leptin were found in 1 study of 20 patients with HG compared with 20 controls as were higher levels of nesfatin-1, another hormone thought to regulate appetite and weight. 52 Of note, the leptin level results in this study differ from what has previously been reported in the literature 53 ; thus, further studies are needed to determine the role of hunger hormones in HG and whether they can serve as a marker for disease severity.…”
Section: Psychologic Factorscontrasting
confidence: 84%
“…We did not find a relationship between NV and leptin in this study, which is consistent with the work of Ozturk Arslan et al (2003) and Unsel et al (2004) but contrasts with the findings of other studies (Aka et al, 2006;Demir et al, 2006). A possible explanation for this apparent discrepancy is, again, the severity of NV.…”
Section: Discussioncontrasting
confidence: 64%
“…We also postulated that some big molecular substances or secretion resulted from unclosed neural tube, particularly in individuals with anencephaly, may play a role in the occurrence of severe NVP. Many researchers have concluded that pregnant women with very severe NVP (i.e., hyperemesis gravidarum) had higher circulating leptin levels than pregnant women without severe NVP (Aka et al, 2006;Chou et al, 2011;Demir et al, 2006). Busbug demonstrated increased leptin levels in maternal serum and amniotic fluid in pregnant women who had fetuses with NTDs compared with a control group (Busbug et al, 2003).…”
Section: Discussionmentioning
confidence: 99%